Experiences of family caregivers regarding the health of children with congenital craniofacial anomalies in Colombia - María Mercedes Lafaurie; Lina María Vargas-Escobar; María Clara González; Herney Alonso Rengifo (PLOS Global Public Health, 2026)
Recognizing the challenges faced by family caregivers regarding the health of children with congenital craniofacial anomalies (CCAs) contributes to strengthening healthcare programs according to patients’ and families’ differential needs. This qualitative study presents the experiences of 25 caregivers of children with CCAs from Bogotá and Cali, Colombia, identified from care registries and consultation statistics provided from public high-complexity healthcare institutions. Grounded in descriptive phenomenology and employing thematic analysis, this research utilized individual interviews and focus group discussions to explore the diagnostic process and its impact, experiences with healthcare services, and the caregiver’s role and daily care activities. Data were analyzed using MAXQDA. qualitative software. Findings highlighted the complexity of caring for children’s health. Challenges included late diagnoses, pessimistic views of the children with CCAs condition by healthcare team members; lack of effective support, information, and guidance from health staff; absence of clear care and referral protocols, and limited access to specific adaptations and timely specialized care for children with CCAs. There were also reduced therapeutic services, and a pronounced gendered caregiving burden when responsibilities fall almost exclusively on mothers. System fragmentation, reflected in deficiencies in communication and a lack of clear, coordinated, and timely pathways of care, as well as the absence of adequate psychosocial support for families, emerged as common structural problems in healthcare services in both geographic settings where this research has been conducted. Gender-sensitive strategies focused on alleviating emotional concerns and the burden of caregiving from diagnosis onward within a patient and family-centered care model are decisive. Improving comprehensive CCAs training for healthcare personnel and adjusting care pathways are suggested to contribute to the implementation of inclusive health programs that address the diverse needs of children and their families.